Analysis of the Impact of Export Duty Policy, Total Production of Cocoa Beans, and Imports of Cocoa Beans on Cocoa Butter Exports in Indonesia - Rheavanya, Sabrina Izzah; M. Taufiq; Utami, Anisa Fitria (PT Inovasi Pratama Internasional, 2024)
The purpose of this research is to analyze the influence of export duty policies, the amount of cocoa bean production and imports of cocoa beans on the volume of cocoa butter exports in the short and long term. This research uses a descriptive approach with quantitative methods, the focus is testing theories using number-based analysis and statistical analysis. The data used is a time series from 1993 to 2022. In this research, the model used is the Error Correction Model (ECM). The ECM method aims to identify the influence of independent variables on the dependent variable in both the short and long term by focusing on the variables of cocoa butter exports, export duty policies, production quantities and imports of cocoa beans. The analytical tool in this research uses Eviews-12. The conclusion of this research is as follows: Export duty policy (dummy variable) in the long term has a significant positive effect on coca butter exports. The amount of cocoa bean production does not have a significant impact on cocoa butter exports, both in the long and short term. The volume of cocoa bean imports has a significant impact on cocoa butter exports, both in the long and short term.